Penetration time of Salmonella Heidelberg through shells of white and brown commercial eggs - Raghiante, F (2010)
This study aimed at determining the minimum time required for the penetration of Salmonella Heidelberg inside the eggs after contact with contaminated material. Recently-collected brown and white eggs from laying hens between 45-50 weeks of age, reared in a commercial poultry house, were artificially contaminated by contact with wood shavings moistened with liquid inoculum of Salmonella Heidelberg in stationary-growth phase (10³-10(4) CFU g-1). According to type (white or brown), eggs were distributed into three different groups, with four replicates each: negative control group (no artificial contamination), positive control group (analyzed externally immediately after contamination and internally after the maximum storage period of the test group) and test group. Eggs were stored at controlled environmental temperature varying from 25ºC to 30ºC. In the test group, eggs contents (yolk and albumen) were pooled and analyzed after 1:00, 1:30, 2:00, 2:30, 3:00, 3:30, and 4:00 hours after contamination for the presence of Salmonella Heidelberg in 25g of this pool. The experimental unit consisted of five eggs in each test. The analysis protocol included pre-enrichment, selective enrichment, plating on selective agar, and biochemical and serological tests. The results obtained were submitted to logistic regression, which indicated that the presence of Salmonella Heidelberg was verified after 2:16 h and 2:44 h of contact with white and brown eggs, respectively.